The mouse popliteal lymph node displays immediate contact with mammary gland ducts - Elenius, Henrik (My University, 2026)
Lymph nodes have a critical role in initiating and regulating adaptive immune responses. They function as gatekeepers of our bodies, being the primary contact point of foreign material and our immune cells. In addition to these immune cells, many subsets of stromal cells are key mediators in immune functions and maintaining lymph node structure. These include lymphatic endothelial cells, blood endothelial cells and fibroblastic reticular cells. The aim of this study was to analyze the effects of vaccinedriven inflammatory responses on the stromal cells of mouse lymph nodes. To define stromal inflammatory changes, mice were immunized using Complete Freund’s adjuvant whereafter popliteal and inguinal lymph nodes were carefully dissected at specific timepoints. CD45-negative non-leukocytic fractions of lymph node cells were enriched and subjected to single-cell RNA sequencing to compare stromal cell transcriptomics between immunized and control conditions. To validate these changes in gene expression at protein level, immunofluorescence staining was performed using fluorescently labeled antibodies, followed by high-resolution confocal imaging. Unexpectedly, a population of epithelial cells was identified in both resting and immunized lymph node samples. Following histological experiments revealed EpCAMpositive duct-like structures in immediate contact with the lymph node capsule. These ducts did not originate from skin accessories, as shown in further multitissue stainings, but did indeed display mammary gland characteristics. In conclusion, this study shows that mammary gland ducts come to close contact of lymph nodes and extend even to the popliteal region. This immediate proximity further suggests that there is a possibility of interaction between these tissues. Thus, this study opens new avenues for future research to dissect cross-talk between lymph nodes and mammary glands.
Keywords: lymph node, mammary gland, immune response, epithelial cells